Resistance Training Reduces Age- and Geography-Related Physical Function Discrepancies in Older Adults. (February 2021) - Baker, Breanne S.; Miller, Kristin; Weitzel, Kelsey J.; Duren, Dana L.; Gammon, Robin; Mills-Gray, Susan; Ball, Stephen D.
Comorbidities affecting physical function increase with advanced-age and rural living. This study investigated the degree of benefit from resistance training (RT) in older adults based on age (50–89 years), location (urban vs. rural), and program duration (10 vs. 8-weeks). 260 participants completed pre- and post-program dynamic and static tasks and flexibility testing. Paired and independent t -tests and one-way and repeated measures ANOVAs were used to test group improvements. All ages improved performance (all p  ≤ .002) but those in their 50's improved flexibility the most and those in their 60's improved 30STS more and tandem balance less than those in their 80's. Both rural and urban participants improved in all areas (all p  ≤ .002), but rural participants reported greater improvements in tandem balance. Both 10- and 8-week classes improved performance (all p  ≤ .001), but 8-week participants improved dynamic tasks and tandem balance more. RT can reduce functional discrepancies in older adults and rural residents.